Pemetaan Sektor Potensial Penunjang Investasi di Kota Surabaya Berbasis Analisis Spasial - Jelita, Jelita; Kistanti, Nurjannah Rahayu (UI Scholars Hub, 2025)
Investment is one of the main pillars in encouraging economic growth in a region. The city of Surabaya, as one of the second largest cities in Indonesia, is an attractive investment destination for many investors. This research aims to map investment potential in the Surabaya City area to support regional economic development by directing investment opportunities in Surabaya City areas with high growth prospects. This research method uses 3 analytical methods to model the spatial pattern of investment in the city of Surabaya, namely the Entropy Weight Method (EWM), Moran’s I and Regional classification. Results show significant variation, with some areas identified as Hot Spots and Sub Hot Spots, indicating high investment potential, while other areas are categorized as Cold Spots and Sub Cold Spots, indicating low investment potential. Several sub-districts are also categorized as Not Significant, indicating areas with lower investment potential or that have not yet become the main focus.